2000
DOI: 10.1128/aac.44.11.3055-3060.2000
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Synergistic Effects of Double and Triple Combinations of β-Lactams, Vancomycin, and Netilmicin against Methicillin-Resistant Staphylococcus aureus Strains

Abstract: Several studies have previously reported synergistic effects between vancomycin and a given ␤-lactam or a given aminoglycoside against methicillin-resistant Staphylococcus aureus (MRSA) strains. The aim of our study was to exhaustively compare the effects of different combinations of a ␤-lactam, vancomycin, and/or an aminoglycoside against 32 clinical MRSA strains with different aminoglycoside susceptibility patterns. The effects of 26 different ␤-lactam-vancomycin and 8 different aminoglycoside-vancomycin com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
42
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(48 citation statements)
references
References 31 publications
5
42
1
Order By: Relevance
“…In both trials, the combination of 1/2 MIC of VAN + 1/2 MIC of IPM was shown to be synergistic, with an average reduction of 5 log CFU/mL for all four selected strains in relation to VAN alone after 24 h of incubation. These results are in agreement with other studies which showed the bactericidal activity of this combination after 24 h of incubation with MRSA strains, using the time-kill curve method (Totsuka et al 1999, Rochon-Edouard et al 2000, Jacqueline et al 2005. There was no significant decrease in log CFU after antimicrobial reapplication, indicating a non-concentration-dependent activity previously described as a pharmacological propriety of β-lactam drugs (Brunton et al 2006).…”
Section: Strainsupporting
confidence: 82%
See 2 more Smart Citations
“…In both trials, the combination of 1/2 MIC of VAN + 1/2 MIC of IPM was shown to be synergistic, with an average reduction of 5 log CFU/mL for all four selected strains in relation to VAN alone after 24 h of incubation. These results are in agreement with other studies which showed the bactericidal activity of this combination after 24 h of incubation with MRSA strains, using the time-kill curve method (Totsuka et al 1999, Rochon-Edouard et al 2000, Jacqueline et al 2005. There was no significant decrease in log CFU after antimicrobial reapplication, indicating a non-concentration-dependent activity previously described as a pharmacological propriety of β-lactam drugs (Brunton et al 2006).…”
Section: Strainsupporting
confidence: 82%
“…Due to a lack of therapeutic options, some studies have focused on the combination of two or more antibiotics as an alternative treatment (Totsuka et al 1999, Rochon-Edouard et al 2000, Kobayashi 2005, Yamaoka 2007, Nguyen & Graber 2010. Promising results in vitro and in vivo could lead to effective therapy along with a reduction of therapeutic doses, adverse effects and treatment duration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This concept is based on several in vitro and animal studies that demonstrated a synergistic effect of vancomycin-␤-lactam combinations against MRSA (6)(7)(8)(9)(10)(11).…”
mentioning
confidence: 99%
“…Penicillin-binding protein 2A (PBP2A) is the protein responsible for the methicillin resistance mechanism in S. aureus. Methicillin resistance confers resistance to all the beta-lactams, including cephalosporins and carbapenems; however, many studies have reported a potent efficacy of imipenem against S. aureus when used in combination with other antimicrobial agents, including fosfomycin (Nakazawa et al, 2003), vancomycin (Totsuka K et al, 1999;Benquan et al, 2002;Rochon-Edouard et al, 2000), and cephalosporins (Uete & Matsuo et al, 1995).…”
Section: Linezolid Plus Carbapenemsmentioning
confidence: 99%